2019
DOI: 10.4040/jkan.2019.49.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Effect of Self-Efficacy on the Relationship between Perceived Self-Management Support and Health-Related Quality of Life among Cancer Survivors

Abstract: This study aimed to examine the levels of perceived self-management support, self-efficacy for self-management, and health-related quality of life (HRQoL) in cancer survivors, and to identify the mediating effect of self-efficacy in the relationship between perceived self-management support and HRQoL. Methods: This study used a descriptive correlational design. Two hundred and four cancer survivors who had completed treatment participated in the study. Measurements included the Patient Assessment of Chronic Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…This measure was used in a previous study which found that higher scores implied higher HRQoL [ 21 ]. Cronbach’s Alpha in this study was 0.81, and was reported as 0.93 in a previous Korean study [ 22 ]. Adherence to the ACS guideline (2012) was estimated by the following categories: (1) achieving and maintaining a healthy body weight using body mass index, (2) engaging in regular physical activity (MET-hours/week), and (3) following the ACS guidelines for cancer prevention (including achievement of a dietary pattern that is high in vegetables, fruits, whole grains, low in processed and red meat, low alcohol intake, and non-smoking).…”
Section: Methodssupporting
confidence: 65%
“…This measure was used in a previous study which found that higher scores implied higher HRQoL [ 21 ]. Cronbach’s Alpha in this study was 0.81, and was reported as 0.93 in a previous Korean study [ 22 ]. Adherence to the ACS guideline (2012) was estimated by the following categories: (1) achieving and maintaining a healthy body weight using body mass index, (2) engaging in regular physical activity (MET-hours/week), and (3) following the ACS guidelines for cancer prevention (including achievement of a dietary pattern that is high in vegetables, fruits, whole grains, low in processed and red meat, low alcohol intake, and non-smoking).…”
Section: Methodssupporting
confidence: 65%
“…According to mapping of the PACIC subscales onto the CCM elements [ 42 ], it is conceptually sound to use the PACIC as a measure of self-management support in care quality assessments. Self-efficacy is an important outcome of self-management support intervention [ 43 ] and was found to be significantly associated with a patient’s perceived self-management support [ 24 , 26 ]. Thus, we expected that the K-PACIC-CS score would be positively correlated with the CSSES-K score.…”
Section: Methodsmentioning
confidence: 99%
“…It has been used to evaluate the delivery of CCM-based intervention for a variety of chronic illness conditions, including diabetes, osteoarthritis, asthma, hypertension, and chronic obstructive pulmonary disease [ 16 21 ]. Several studies have demonstrated that the PACIC is an acceptable, valid, and reliable instrument [ 14 , 15 , 22 – 25 ], and it is associated with measures of self-management behavior [ 16 , 20 ], self-efficacy [ 24 , 26 ], and health-related quality of life (HRQOL) [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer survivors must continuously manage their health by ceasing smoking, reducing alcohol consumption, exercising, and eating a healthy diet to prevent complications of cancer treatment and recurrence [6]. Self-efficacy positively affects the QOL of patients with breast cancer by allowing them to actively cope with health issues related to breast cancer [14,15] and engage in healthy self-care behaviors [13,14,16,17]. Social support is also a major environmental factor that affects the QOL of patients with breast cancer.…”
Section: Plos Onementioning
confidence: 99%
“…Major factors that affect breast cancer patients' QOL after their completion of the primary treatment include physical and psychological symptoms [10][11][12], self-efficacy [13][14][15], and social support [16][17][18]. Symptom experience is an especially important factor in the QOL of patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%